An Analysis of Derivational and Inflectional Morphemes Found in Kamala Harris’ Speech - Guna, Stanislaus; Sartitin, Lidia; Ely Heldiana Selamat (Rainbow : Journal of Literature, Linguistics and Culture Studies, 2025)
This study aims to know the types and analyze the functions of derivational and inflectional morphemes contained in Kamala Harris' speech. The researcher uses qualitative method with descriptive approach to analyze the data. The data analyzed in this research are derivational and inflectional morphemes that appear in Kamala Harris' speech transcripts, which were obtained by transcribing her speeches and identifying relevant words containing these morphemes. The researcher acts as the main instrument in this research. The data were collected by downloading the speech video, transcribing the speech, identifying words containing derivational and inflectional morphemes, classifying them into their respective types, and analyzing their functions. At the end of the analysis, the researcher draws conclusions based on the types and functions of the derivational and inflectional morphemes used. The findings reveal that a total of 330 words contain derivational and inflectional morphemes, consisting of 120 derivational morphemes and 213 inflectional morphemes. The derivational morphemes were categorized into nine types; 20 adjectives to noun, 19 nouns to adjective, 25 verbs to noun, 1 noun to verb, 17 verbs to adjective, 1 adjective to verb, 17 adjectives to adverb, 6 adjectives to adjective, and 14 nouns to noun. In terms of function, these derivational morphemes contributed to 59 noun formation, 42 adjective formation, 2 verb formation, and 17 adverb formation. The inflectional morphemes were classified into seven types; 110 plural, 46 past tense, 23 third person singular present, 16 past participle, 6 progressive form, 6 possessive, and 6 superlatives. The inflectional functions are 110 function as plural, 46 as past tense, 23 as third-person singular present, 16 as past participle, 6 as progressive, 6 as possessive, and 6 as superlative. The researcher concludes that derivational morphemes play a role in the formation of new word classes, while inflectional morphemes serve to indicate grammatical aspects such as number, time, and possession. These two types of morphemes not only clarify the grammatical structure but also enrich the vocabulary in English, which ultimately improves the clarity of communication.